2014
DOI: 10.1049/iet-pel.2013.0405
|View full text |Cite
|
Sign up to set email alerts
|

Control of a three‐phase AC/DC VIENNA converter based on the sliding mode loss‐free resistor approach

Abstract: The three-phase VIENNA rectifier supplying a regulated DC bus in a micro-grid architecture is controlled in this study by means of a sliding-mode regulation loop, which imposes a loss-free resistor (LFR) behaviour in each phase for power factor correction. Assuming equal parameters per phase and that the intermediate node between the output capacitors of the DC link is the neutral point of the AC generator, the rectifier can then be modelled as a tetra-port LFR with three decoupled resistive input ports and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…T^s w (z) Finally, note that the effective hysteresis band is the result of adding algebraically to the constant value given by (22) the corresponding corrections introduced by the switching period regulation loop. Fig.…”
Section: Analysis Of the Proposed Examplementioning
confidence: 99%
“…T^s w (z) Finally, note that the effective hysteresis band is the result of adding algebraically to the constant value given by (22) the corresponding corrections introduced by the switching period regulation loop. Fig.…”
Section: Analysis Of the Proposed Examplementioning
confidence: 99%
“…The corresponding control law has been designed by means of the sliding-mode control theory [27,[30][31][32][33] in order to describe the dynamic behaviour of the system employing a hysteretic modulator in the feedback loop when sliding motions can be induced.…”
Section: Research Articlementioning
confidence: 99%
“…It has been demonstrated that this technique is able to track periodic references, forcing loss-free resistor behavior. This implies resistive behavior at the input port and power source behavior at the output port of a power converter [30], which in fact transforms the set rectifier-load into a virtual resistance, as it is successfully developed for a semi-bridge-less pre-regulator in the work of [31] and a three-phase HPF Vienna rectifier in the work of [32]. As in the case of the grid-connected inverters, the control must track a reference, which can be directly provided by a measurement of the input voltage or indirectly by a synchronized reference generator [33].…”
Section: Introductionmentioning
confidence: 99%